2017
DOI: 10.7872/crya/v38.iss4.2017.285
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Cyanobacterial Diversity in the Giant Cave (Trieste, Italy): The New GenusTimaviella(Leptolyngbyaceae)

Abstract: T he microflora of hypogean environments has been studied increasingly worldwide. However, some sites have hardly been examined or not studied at all; this is the case for the Giant Cave, a Karst show cave located near Trieste, Italy. In the present study we began characterizing the Giant Cave Lampenflora by using a polyphasic approach, focusing, in particular, on three Leptolyngbya-like strains named GR2, GR4, and GR13. Light and electron microscopic observations were carried out and the water-soluble pigment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…2014, Sciuto et al. 2017, Sendall and McGregor 2018, Nakayama et al. 2019) which may require further conceptual changes in future cyanobacterial taxonomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2014, Sciuto et al. 2017, Sendall and McGregor 2018, Nakayama et al. 2019) which may require further conceptual changes in future cyanobacterial taxonomy.…”
Section: Discussionmentioning
confidence: 99%
“…These are: aerotopes that first appeared in Pseudanabaenales and can be found in many orders; attenuation of end cells in trichal types; nitrogen fixation in Synechococcales, Nodosilineales, Oscillatoriales, Chroococcales, or Nostocales; gliding motility present in the filamentous genera throughout the tree of life. To make the case even more complicated, a number of recent studies have reported morphologically cryptic species and genera based on 16S rRNA plus ITS analyses (Osorio-Santos et al 2014, Sciuto et al 2017, Sendall and McGregor 2018, Nakayama et al 2019) which may require further conceptual changes in future cyanobacterial taxonomy.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, this genus of cyanobacteria was insufficiently studied and lacked a molecular definition, but lately, it was proven to colonize stone surfaces and rocks, as well as lakeshores and the surfaces of freshwater sponges in the Baikal lake [ 38 ]. The Timaviella , which was the most abundant in one of the samples of the cave walls in our study, is a recently described genus characteristic of a cave ecosystem, and the representatives of this genus (Timaviella circinata and Timaviella karstica ) have previously been isolated from the Giant Cave lampenflora in Italy under typical cave conditions, characterized by high humidity and constant temperature [ 39 ]. Since this newly described genus consists of few more species recently described ( T. obliquedivisa , T. radians , Timaviella sp.…”
Section: Discussionmentioning
confidence: 99%
“…Subaerial habitats, caves, and hypogea have been a great source of Oculatellaceae. For example, Oculatella subterranea (Zammit et al, 2012), Oculatella kauaiensis (Osorio‐Santos et al, 2014), Albertania skiophila (Zammit, 2018), Timaviella circinate , and Timaviella karstica (Sciuto et al, 2017) were all found in cave entrances or hypogea with artificial lighting. Wet walls and frequently wetted hard surfaces represent subaerial habitats, which also have many species, such as Oculatella cataractarum (Osorio‐Santos et al, 2014), Cartusia fontana , Drouetiella fasciculata , D. hepatica , D. lurida , Kaiparowitsia implicata , Komarkovaea angustata , Pegethrix bostrychoides , P. convoluta, P. indistincta , P. olivacea , Timaviella obliquedivisa , Tim.…”
Section: Discussionmentioning
confidence: 99%